2020
DOI: 10.1002/gcc.22849
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive morphologic variants of mantle cell lymphoma characterized with high genomic instability showing frequent chromothripsis, CDKN2A/B loss, and TP53 mutations: A multi‐institutional study

Abstract: Aggressive morphologic variants of mantle cell lymphoma (MCL), including blastoid and pleomorphic (B/P-MCL), are rare and associated with poor clinical outcomes.The genomic landscape of these variants remains incompletely explored. In this multi-institutional study, we describe recurrent mutations and novel genomic copy number alterations (CNAs) in B/P-MCL, using next generation sequencing and SNParray. Chromothripsis, a recently described phenomenon of massive chromosomal rearrangements, was identified in eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 54 publications
4
15
0
Order By: Relevance
“…Currently, the main prognostic factors for MCL patients include age, MIPI, histology, TP53 aberrations and tumor proliferation. When comparing cases with blastoid/pleomorphic vs. classic morphology and high vs. low proliferation rate measured by Ki-67 expression, we observed that TP53 and ATM were the most frequently altered genes in aggressive morphologic variants, being mutually exclusive, which has been shown previously [20]. FAT4, CCND1, SAMHD1, UBR,5 and FAT3 genes were mutated only in nonaggressive cases, i.e.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Currently, the main prognostic factors for MCL patients include age, MIPI, histology, TP53 aberrations and tumor proliferation. When comparing cases with blastoid/pleomorphic vs. classic morphology and high vs. low proliferation rate measured by Ki-67 expression, we observed that TP53 and ATM were the most frequently altered genes in aggressive morphologic variants, being mutually exclusive, which has been shown previously [20]. FAT4, CCND1, SAMHD1, UBR,5 and FAT3 genes were mutated only in nonaggressive cases, i.e.…”
Section: Discussionsupporting
confidence: 77%
“…The genetic landscape of MCL has been investigated in previous studies, although the total number of sequenced samples remains low. To our knowledge, previous larger targeting panel/global sequencing studies (studies with more than 50 studied genes) [4][5][6]17,18,[20][21][22] include only approximately 300 de novo MCL patients in total. Thus, our data on 77 patients is a significant addition to the general knowledge base of the frequency of genetic alterations in MCL.…”
Section: Discussionmentioning
confidence: 99%
“…Subanalysis of these patients is given in Table S5. Recently, Streich et al reported that MCL with blastoid and pleomorphic morphology frequently harbor both TP53 and CDKN2A/B aberrations, and that these cases are characterized by frequent chromothripsis [24]. Curiously, in sharp contrast to MCL, aberrations of TP53 and CDKN2A were mutually exclusive in Burkitt lymphoma and were very rarely observed in diffuse large B cell lymphoma [25][26][27].…”
Section: Concurrent Aberration Of Tp53 and Deletion Of Cdkn2a Is Assomentioning
confidence: 99%
“…On the contrary, all molecular laboratories are today equipped for the mutational screening of TP53. TP53 mutation has been reported in 62% of MCL blastoid/pleomorphic variants [39] and in 20-28% of MCL nodal type, either in clonal or subclonal form [40]. Recent studies have demonstrated the strong negative impact of TP53 mutations on outcome of MCL patients, in terms of worse EFS and OS [2,41].…”
Section: Allo-sct As An Option For "Very High Risk" Patientsmentioning
confidence: 99%